What constitutes health care seeking pathway of TB patients: A qualitative study in rural Bangladesh - Shatil, Tanvir; Khan, Nusrat; Yunus, Fakir Md.; Chowdhury, Anita Sharif; Reza, Saifur; Islam, Shayla; Islam, Akramul; Rahman, Mahfuzar (Atlantis Press, 2022)
This article was published in The Journal of Epidemiology and Global Health [©2019 Published by Atlantis Press, part of Springer Nature, Open access, licensed under CC BY-NC-ND 4.0 ] and the definite version is available at: https://doi.org/10.2991/jegh.k.190929.001 The Article's website is at: https://www.atlantis-press.com/journals/jegh/125919254/view